Ideas for science projects - Gardner, Robert, 1929- (New York : F. Watts, 1986)
Introduces the scientific method through instructions for observations and experiments in biology, physics, astronomy, botany, psychology, and chemistry.
Includes index.
Bibliography: p. 142.
Booklist.
Wilson's Senior High School.
8.0
8.0
Keywords: Science projects -- Juvenile literature; Experiments; Science -- Experiments; Science -- Experiments